Response to Haskell's "Academic Freedom ... & Student Evaluation" - Stake, Jeffrey E. (Education Policy Analysis Archives, 1997)
Haskell (1997) argued that the administrative practice of student evaluation of faculty is a threat to academic freedom. However, before that claim can be substantiated, several prior questions must be addressed: To whom does academic freedom belong? Individual faculty? The academy? Whose actions can violate the right? Can any lines be drawn based on whether the substance or form of classroom behavior is influenced? And still another crucial point is whether a body can violate academic freedom without any intent to interfere with or control the substance of what is said to students.